EFFECTIVENESS OF PADLET MEDIA USE FOR BEGINNER LEVEL BIPA LEARNING - Nugraheni, Luthfa; Ristiyani, Ristiyani; Setiawati, Rani; Sumaji, Sumaji (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
This study aims to describe the effectiveness of using padlet media in beginner-level BIPA learning. This type of research is experimental. The research sample for this study was BIPA students at Muria Kudus University, totaling 27 people. The data in this study are the results of BIPA learning using Padlet media. Data analysis techniques at this stage used descriptive and inferential statistical analysis. The results showed that Padlet media was effectively used in learning beginner-level BIPA at Muria Kudus University. Students' beginner-level BIPA learning outcomes improved by using Padlet media compared to before using the media. Padlet Media provides feedback, information exchange, and portfolio documentation for learning implementation.